The municipal and county council survey (KOLFU) 2008 - Gilljam, Mikael; Karlsson, David; Sundell, Anders (University of Gothenburg, 2015)
KOLFU is a survey addressed to all members of Sweden's 20 county councils and 290 municipal councils (a total of about 13 500 people). KOLFU was conducted for the first time in 2008-2009 (KOLFU 2008). The actual number of respondents was 9 890.

KOLFU 2008 was conducted by a research team at the University of Gothenburg, while the company Detector AB was responsible for the fieldwork. The survey was conducted as part of the project "Politiker tycker om demokrati". The research team consisted of Mikael Gilljam (project manager), David Karlsson and Anders Sundell. KOLFU includes questions on the representatives' social background, their opinions on political issues, their view on the rules of democracy and the political process in their own municipality and county council.

The results from KOLFU 2008 are presented in the book "Politik på hemmaplan. Tiotusen fullmäktigeledamöter tycker om politik och demokrati" (Gilljam, et al., 2010a), among others.

Purpose:

The municipal and county council survey (KOLFU) 2008 aims to study Swedish local and regional political representatives' attitudes on democracy and politics.

KOLFU är en undersökning som riktar sig till samtliga fullmäktigeledamöter i Sveriges 20 landsting och 290 kommuner (totalt cirka 13 500 personer). KOLFU genomfördes för första gången 2008-2009 (KOLFU 2008). Antalet faktiska respondenter - exklusive bortfallet - var 9 890 .

KOLFU 2008 genomfördes av ett forskarteam vid Göteborgs universitet medan företaget Detector AB svarade för fältarbetet. Undersökningen genomfördes inom ramen för projektet Politiker tycker om demokrati. Forskarteamet bestod av Mikael Gilljam (projektledare), David Karlsson och Anders Sundell. I KOLFU ingår frågor om ledamöternas sociala bakgrund, deras åsikter i politiska frågor, deras syn på demokratins spelregler och det politiska arbetet i den egna kommunen och landstinget.

Resultat från KOLFU 2008 har presenterats i bland annat boken "Politik på hemmaplan. Tiotusen fullmäktigeledamöter tycker om politik och demokrati" (Gilljam et al., 2010a).

Syfte:

Kommun- och landstingsfullmäktigeundersökningen (KOLFU) 2008 genomfördes för att undersöka svenska kommun- och landstingspolitikers syn på demokrati och politik.
Kommun- och landstingsfullmäktigeundersökningen (KOLFU) 2008
Keywords: LOCAL GOVERNMENT POLICY; KOMMUNALPOLITIK; POLITICAL BEHAVIOUR; POLITISKT BETEENDE; DEMOCRACY; DEMOKRATI; INTERNAL POLITICS; INRIKESPOLITIK; POLITICAL REPRESENTATION; POLITISK REPRESENTATION; POLITICAL PARTIES; POLITISKA PARTIER; REGIONAL POLICY; REGIONALPOLITIK; POLITICIANS; POLITIKER; REPRESENTATIVE DEMOCRACY; REPRESENTATIV DEMOKRATI; POLITICS; POLITIK; Political behaviour and attitudes; Politiska beteenden och attityder; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap